WORLD WONDERS : discover the secrets of our planet's iconic structures - Gaszynski, Michal (Bishopbriggs, Glasgrow : Collins, an imprint of HarperCollins Publishers, 2019)
"The greatest structures in human history. Explore the constructions that have shaped our world and learn their hidden secrets in this large format highly illustrated book. Each building analysed by the author is illustrated with its architectural details and enriched with intriguing facts, symbols and infographics"--Provided by publisher.
Includes index.
Keywords: Architecture; Architecture -- Pictorial works; Buildings; Pictorial works